Taxas de geração de viagens para instituições privadas de ensino superior de Uberlândia, MG - Paula, Ana Flávia Ferreira de Castro (2013)
The number of studies that assess the impact of travel, performed by users, in the traffic surrounding universities in Brazil is still small. Thus, the objective of this study was to estimate the trip generation rates for the motorized and non-motorized travel modes, which are used by students, teachers, and employees of private Universities of Uberlândia, Minas Gerais. For this purpose, a survey was applied to the university community of four universities of the city. Rates were estimated for the trips attracted and produced by students for transportation modes: bus and van, car, motorcycle, and on foot and by bicycle for the morning, afternoon and evening periods. The survey result indicated the following average attraction rates: transportation mode bus and van (0.522), automobile (0.325), motorcycle (0.100), and on foot and by bicycle (0.057). Regarding the average production rates the result was: transportation mode bus and van (0.507), automobile (0.362), motorcycle (0.109), and on foot and by bicycle (0.056). For the transportation mode on foot and by bicycle the calculated standard error was very high, then, it is recommend using the rates with caution until further studies are carried out and the results compared.